Innovative braking system for high-speed 80-foot platform - V. A. Nikonov; V. F. Zubkov; M. N. Tsibizov; I. V. Nazarov; D. V. Gorskiy (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
The article discusses technical solutions for the creation of an effective design of a brake system for high-speed longwheelbase platforms intended for the transport of containers, as well as for the development of a fundamentally new brake equipment for the pneumatic, electro-pneumatic and mechanical parts of the brake system. Modular braking equipment for the pneumatic and electro-pneumatic parts of the high-speed platform braking system, compactly located under the platform frame, provides technical compatibility when controlling platform brakes as part of not only a high-speed freight train of permanent formation, but also in trains for other purposes, regardless of the location of the platform in the composition of the train. The performance of the braking equipment of each platform in motion and in the parking lot is monitored using pressure sensors and an electronic unit that processes the readings of the sensors and transmits information to the locomotive via one of the wire lines of the electro-pneumatic brake. The brake rigging used on the high-speed platform is arranged in the design of three-axle bogies and provides doublesided pressing on the wheels with typical composite brake pads, automatic regulation and maintenance of the standard clearances between brake pads and wheels. The proposed promising technical solutions make it possible to continuously diagnose the parameters of the brakes of each platform as part of a permanent train, display them on the locomotive monitor and transmit them to the dispatch centers of the Russian Railways infrastructure. Thanks to this, the braking effciency can be increased and the safety of train traffc can be ensured while increasing the permissible travel speeds. In the modern concept of digitalization of the infrastructure of Russian Railways, which provides for the creation in 2021–2025 (and in the future until 2030) of cars in which intelligent technologies should be applied, the braking system of a high-speed platform can be considered as the basis for creating a digitally controlled train — one of the key elements of the digital railway.